Penilaian Efektivitas Pelatihan Bagi Peningkatan Prestasi Kerja Karyawan (Penelitian pada 100 Orang Karyawan Swasta di Kota Pontianak) - Pasifikus Maisirata (President University, 2019)
Training is a systematic process of changing the behavior of employees in a direction to improve organizational goals. Quality employees are not created by themselves. Education and training is one of the important tools in supporting the improvement of work performance of employees. Education and training not only adds knowledge but can also improve work skills and will ultimately affect productivity improvements. The purpose of the company is to improve the quality and performance of its employees. Therefore, the Company engages its employees in training in the hope of bringing positive changes to the company. In this study the authors used descriptive methods. Data collection techniques used were observation, questionnaires, and documentary studies. The population in this study included private employees who worked in the city of Pontianak. Because the population in this study is less than one hundred, the entire population is sampled. The conclusion in this study is that the employee training policy of the employees studied in the city of Pontianak has been running well. Where in the employee training policy an overview of the work, knowledge, skills and expertise in the work is given.